Darwinian Goggles: Why the Human Brain Did Not Evolve to Accurately Represent the True Nature of Reality. - JOHNSTON, VICTOR S. (Skeptic, 2019)
The article argues why the human brain did not evolve to accurately represent the true nature of reality. It reports that the brain evolved for the sole purpose of enhancing the survival of human genes, and discusses how Darwinian perspective has profound implications for understanding the functional value of human conscious experiences.